Early rebleeding increases mortality of variecal bleeders on secondary prophylaxis with β-blockers and ligation. Issue 9 (September 2020) - Ardevol, Alba; Alvarado-Tapias, Edilmar; Garcia-Guix, Marta; Brujats, Anna; Gonzalez, Laura; Hernández-Gea, Virginia; Aracil, Carles; Pavel, Oana; Cuyas, Berta; Graupera, Isabel; Colomo, Alan; Poca, Maria; et al.
Abstract: Background/aims: Despite secondary-prophylaxis with β-blockers and endoscopic-variceal-ligation rebleeding is frequent, particularly within the first-6-weeks. Early-rebleeding may have greater impact on death-risk than late rebleeding, which may affect therapy. We assessed whether the influence of rebleeding on long-term survival of patients on secondary-prophylaxis is greater in patients with early-rebleeding. Methods: 369 patients with cirrhosis were consecutively included once recovered from first variceal-bleeding. The impact of rebleeding on survival was investigated according to whether it occurred within 6-weeks (early-rebleeding) or later (late-rebleeding). Results: During 46-months of follow-up (IQR: 14-61), 45 patients (12%) had early-rebleeding, 74(20%) had late-rebleeding and 250(68%) had not rebleeding. Mortality risk was higher in early-rebleeding group vs. late-rebleeding (HR = 0.476, 95%CI = 0.318–0.712, p < 0.001) and was similar in late-rebleeding group vs. no-rebleeding (HR = 0.902, 95%CI = 0.749–1.086, p = 0.271). Adjusting for baseline risk-factors, early-rebleeding was independently associated with mortality-risk (HR = 1.58, 95%CI = 1.02–2.45; p = 0.04). Child-Pugh&MELD scores improved at 3rd-4th-week only in patients without early-rebleeding ( p < 0.05). Presence of ascites or encephalopathy, MELD-score>12 and HVPG>20 mmHg identified patients at risk of early-rebleeding. Conclusions: Patients with early-rebleeding have higher risk of death than patients without rebleeding and even than those rebleeding later. Our results suggest that patients at risk of early rebleeding might benefit from preemptive therapies such as early-TIPS.